2020
DOI: 10.1101/2020.06.15.153080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving oligo-conjugated antibody signal in multimodal single-cell analysis

Abstract: Simultaneous measurement of surface proteins and gene expression within single cells offers highresolution snapshots of complex cell populations. These methods rely on staining cells with oligoconjugated antibodies analogous to staining for flow-and mass cytometry. Unlike flow-and mass cytometry, signal from oligo-conjugated antibodies is not hampered by spectral overlap or limited by the number of metal isotopes, making it a highly sensitive and scalable approach. Signal from oligoconjugated antibodies is qua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Analysis of the median adt value for each cluster revealed that each Total-Seq antibody produced a substantial background read count (Figure 4B). This is in line with observations by others when using high antibody concentrations as recommended in suppliers' protocols (Buus et al, 2021). Comparing the characteristic features of cDC1 (CD8A, CD24, XCR1) against those of cDC2 (CD11B, CD172A, CD4) in this way revealed that the expression of these markers was largely restricted to a single-cell type (Figure 4B).…”
Section: Simultaneous Detection Of Transcript and Epitope Enables Confident Cdc Lineage Identificationsupporting
confidence: 90%
“…Analysis of the median adt value for each cluster revealed that each Total-Seq antibody produced a substantial background read count (Figure 4B). This is in line with observations by others when using high antibody concentrations as recommended in suppliers' protocols (Buus et al, 2021). Comparing the characteristic features of cDC1 (CD8A, CD24, XCR1) against those of cDC2 (CD11B, CD172A, CD4) in this way revealed that the expression of these markers was largely restricted to a single-cell type (Figure 4B).…”
Section: Simultaneous Detection Of Transcript and Epitope Enables Confident Cdc Lineage Identificationsupporting
confidence: 90%
“…To do this, peripheral blood mononuclear cells (PBMCs) were multiplexed and processed using 5' droplet-based scRNA-seq technology (10x Genomics). Surface marker phenotypes were detected using an optimized 60 antibody CITE-seq panel (Buus et al, 2020), generating matching transcriptional and surface protein data. In addition, single-cell T cell receptor (TCR) αβ and γδ, as well as B cell receptor (BCR), sequencing was performed for each sample to evaluate antigen receptor repertoires.…”
Section: Overview Of Immune Responses To Covid-19 Infection and Immunizationmentioning
confidence: 99%
“…Finally, deciding whether a cell is positive or negative for a given marker requires choosing a threshold which often is not clearly evident from the data, given the potentially high level of background noise resulting from imperfect antibody staining. Antibody titrating is resource-intensive and therefore commonly not performed, resulting in lower-than-ideal data quality 37 .…”
Section: Discussionmentioning
confidence: 99%